2014
DOI: 10.1007/s12539-014-0208-y
|View full text |Cite
|
Sign up to set email alerts
|

Design of potential RNAi (miRNA and siRNA) molecules for Middle East respiratory syndrome coronavirus (MERS-CoV) gene silencing by computational method

Abstract: The Middle East respiratory syndrome coronavirus (MERS-CoV) is a virus that manifests itself in viral infection with fever, cough, shortness of breath, renal failure and severe acute pneumonia, which often result in a fatal outcome. MERS-CoV has been shown to spread between people who are in close contact. Transmission from infected patients to healthcare personnel has also been observed and is irredeemable with present technology. Genetic studies on MERS-CoV have shown that ORF 1ab encodes replicase polyprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 37 publications
0
32
0
Order By: Relevance
“…GO-based gene enrichment analysis demonstrated that many biological processes are closely related to the immune response (Figure 2A), including myeloid cell activation and neutrophil activation (Figure 4C and 4E). Interestingly, miRNAs-related gene pathway was overexpressed as a response to COVID-19 infection, which is known to play an important role against viral infection (Nur et al 2015). Activation of miRNAs as a defense mechanism during lung infection could be related to its important role in physiological and pathological processes in the lung (Tomankova et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…GO-based gene enrichment analysis demonstrated that many biological processes are closely related to the immune response (Figure 2A), including myeloid cell activation and neutrophil activation (Figure 4C and 4E). Interestingly, miRNAs-related gene pathway was overexpressed as a response to COVID-19 infection, which is known to play an important role against viral infection (Nur et al 2015). Activation of miRNAs as a defense mechanism during lung infection could be related to its important role in physiological and pathological processes in the lung (Tomankova et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…So far, a number of experimental rules on siRNA duplex features have been frequently reported. These include the asymmetry rules for siRNA duplex ends, high A/U content at the 5'-end of the antisense strand, high G/C content at the 5'-end of sense strand, 30-50% GC content, thermodynamic properties in term of the secondary structures, accessibilities of siRNA and target mRNA of gene(s) of interest (Nur et al, 2014). Therefore, the plant short small RNA interfering tool (pssRNAit web tool), which provides a functional and an off-target minimized siRNA design, was used to in-silico identifying efficient siRNAs candidates in the target mRNAs (Http://plantgrn.noble.org/pssRNAit/).…”
Section: Determination Of Multiple Sirna Candidatesmentioning
confidence: 99%
“…The DNA/RNA GC content calculator (http://www.endmemo.com/Tools/Biology) was used to calculate the GC content of the predicted siRNA. For checking any off-target sequence resemblance in other non-targeted organism's genome, the BLAST tool (http://www.ncbi.nlm.nih.gov/blast) was used against the whole GenBank database by applying expected thresholds value 10 and BLOSUM 62 matrix as parameter (Nur et al, 2014).…”
Section: Gc Calculation and Off-target Alignmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this property of miRNA, attempts have been made to regulate the expression of viral genes using natural miRNAs or by creating synthetic small interfering RNAs (siRNAs) [4][5][6]. In some cases, this approach gave a positive result in vitro but was not applicable in vivo for several reasons, including the lack of evidence that miRNA and siRNA do not have side effects in humans or experimental animals [7][8][9][10].…”
mentioning
confidence: 99%